Exploring the Chasm: Vision-mission Gap and Organizational performance at PT. Telkom from an Educational Perspective - Setiawati, Erlina; Fita Fitriana, Herna; Ayatulloh; Munawaroh (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to analyze the gap between vision and mission and organizational performance at PT. Telkom through a literature review approach. A vision and mission is a strategic foundation that defines the long-term direction and goals of an organization. However, there is often a mismatch between the vision-mission statement and its implementation, which often becomes the main obstacle in achieving optimal performance. The research results show that internal communication, leadership, organizational culture and performance measurement systems have a significant influence on the success of implementing the vision and mission. The gaps that occur can affect employee satisfaction, customer loyalty and organizational competitiveness. Recommendations that can be given through this article are the importance of routine vision and mission evaluation, involving employees in strategy formulation and implementing a performance measurement system that is in line with strategic goals. Thus, this research provides relevant insights for practitioners and academics to understand and overcome challenges related to the vision-mission gap in large organizations such as PT. Telkom.